Agency and Resilience Along the Arizona-Sonora Border: How Unauthorized Migrants Become Aware of and Resist Contemporary U.S. Nativist Mobilization. (11th September 2017) - Martínez, Daniel E; Ward, Matthew H
Abstract: Little is known about the extra-political consequences of contemporary U.S.-based nativist mobilization as well as the resilience unauthorized migrants display in the face of anti-immigrant mobilization along the U.S.-Mexico border. Bringing together social movements and immigration literatures, we examine these interrelated issues using original survey data from the first wave of the Migrant Border Crossing Study. In so doing, we examine: (1) factors influencing repatriated unauthorized migrants' awareness of nativist mobilization (i.e., Minutemen) along the Arizona-Sonora border, and (2) factors explaining why some migrants would or would not be potentially deterred from attempting future unauthorized crossings if encountering the Minutemen were a possibility. Results from a Heckman probit selection model indicate that higher levels of general, financial, and migration-specific human capital are associated with awareness of the Minutemen, while higher household income and status as an indigenous language speaker predict who would be less likely to be deterred from crossing. We also uncover an interesting paradox: migrants traveling with coyotes were less likely to have heard of Minutemen and more likely to be potentially deterred. Collectively, our results provide insight into the overlooked extra-political consequences of contemporary U.S. nativist mobilization, how resiliency in the face of such a deterrent is structured among repatriated unauthorized migrants, and how seemingly powerless migrant groups can mitigate potential threats initiated by relatively privileged groups of U.S. citizens.